Extracorporeal membrane oxygenation for severe acute respiratory distress syndrome associated with COVID-19. Issue 1 (March 2021) - Arikan, Huseyin; Cordingley, Jeremy
Since the first cases were reported in Wuhan, China, in December 2019, coronavirus disease 2019 (COVID-19) has become a pandemic affecting millions of people. As of November 10, 2020, over 49.7 million cases and over 1.2 million deaths have been reported globally since the start of the pandemic [1]. Early reports from China revealed that COVID-19 could range from an asymptomatic state to severe lung involvement progressing to acute respiratory distress syndrome (ARDS). Wu et al. [2] reported that 81% of cases were mild, 14% were severe and 5% were critical. Management of patients who developed ARDS is especially challenging. Several treatment guidelines were proposed during the pandemic [3, 4] and have been updated frequently in accordance with emerging evidence. Extracorporeal membrane oxygenation (ECMO) has already been used for ARDS resulting from other causes. At the beginning of the pandemic certain organisations recommended using ECMO on severe cases of COVID-19 [5, 6]. However, data from large patient populations were missing and initial reports of COVID-19 ECMO support had high mortality rates [7, 8]. These reports were not from specialised centres and patient selection for ECMO remained uncertain. For this reason, Schmidt et al. [9] performed a retrospective cohort study in a specialised referral ECMO centre. ECMO management of severe ARDS patients with COVID-19, who are not responding to lung protective ventilation and salvage strategies like prone positioning or inhaled nitric oxide, is safe if performed in a dedicated referral centre. https://bit.ly/3p5HOEN